Carrier Development Effect on Work Satisfaction and Employee Performance - Anisa Noviyanti; Dian Alfia Purwandari; Tantri Yanuar R Syah (Penerbit Kemala Indonesia, 2019)
This study aims to analyse career development influencing turnover on reward over career development affecting on job satisfaction. The correspondent survey was used in this study over contract employees in the Indonesian Conventional Bank, which is have 25 million employees. The number of correspondent survey was used to analyse using SEM method with LISREL 8.0 program over 255 employees. The analytical model was used in this research to descriptive the analysis result. The results of this study are expected to be able to prove the relationship between career development and reward for the turnover intention in Indonesian contract employees in the Conventional Bank with job satisfaction by intervening variable. The result shows the basis of company policy to reduce the level of turnover intention in contract employees through by improving career development, giving fair rewards, and creating satisfactory working conditions.